Provider perspectives of the introduction and implementation of care for drug-resistant tuberculosis patients in district-level facilities in South Africa: a qualitative study - Vanleeuw, Lieve (BMJ Open, 2020)
OBJECTIVES: Drug-resistant tuberculosis (DR-TB) is a growing concern in many low-income and middle-income countries. Facing rising numbers of DR-TB patients, South Africa (SA) introduced a decentralised model of care for DR-TB in 2011. We aimed to document the introduction and implementation of the new models of care for patients with DR-TB in four provinces (Northern Cape, KwaZulu-Natal, Eastern Cape and Gauteng) in 2015 using mixed methods, including interviews, register reviews and clinical audits. This paper reports on the qualitative component of the study. DESIGN: This is a qualitative interview study. SETTING: Data were collected in 22 decentralised DR-TB sites, primary healthcare facilities and district hospitals and one provincial central DR-TB hospital. PARTICIPANTS: 58 healthcare workers (HCWs), facility staff and provincial and district TB coordinators were included in qualitative interviews. RESULTS: HCWs felt that the introduction of DR-TB care in their facility came with little warning or engagement, creating fear and anxiety. They expressed a need for support from the district and province to guide them through the changes but this support was often lacking. In addition, many respondents expressed feeling isolated and not supported by other healthcare providers which they feel impacts on the quality of the care they provide. CONCLUSION: Introduction of a new service such as DR-TB care can be difficult and does not always result in the intended outcomes. Improved engagement with front-line providers and addressing the fear and anxiety that may be raised by changes in daily practices should be addressed to ensure successful implementation and prevent negative consequences that can hamper quality of care for patients. Attention should be paid to how the decentralised DR-TB unit can be supported by district management and other healthcare providers.